Reaping efficiency gains through product market reforms in China - Molnar, Margit (OECD Publishing, 2022)
The impressive emergence of China's economy is set to lose some momentum as the country catches up with more advanced economies and its rapid ageing also weighs on it. However, China can still reap the "reform dividend", especially with measures to keep up the sustained growth of productivity. Reforms that enhance competition in product markets are among those that can potentially bring about significant productivity gains. China has been lowering the burden on start-ups and simplifying administrative procedures for a while already, achieving significant progress, though more procedures could go online and a one-stop shop is still to be implemented across the country. State ownership remains dominant in most network industries and there are many SOEs even in commercially-oriented industries such as retail or catering. SOEs enjoy implicit government guarantees and are the main beneficiaries of administrative monopolies, i.e. exclusive rights granted by regulations.
Keywords: Economics; China, People's Republic